Differing responses of three Southern Ocean Emiliania huxleyi ecotypes to changing seawater carbonate chemistry - Muller, MN; Trull, T; Gustaaf Hallegraeff (2015)
The invasion of anthropogenic carbon dioxide into the surface ocean is altering seawater carbonate speciation, a process commonly called ocean acidification. The high latitude waters of the Southern Ocean are one of the primary and most severely affected regions. Coccolithophores are an important phytoplankton group, responsible for the majority of pelagic calcium carbonate production in the world’s oceans, with a distribution that ranges from tropical to polar waters. Emiliania huxleyi is numerically the most abundant coccolithophore species and appears in several different ecotypes. We tested the effects of ocean acidification on 3 carefully selected E. huxleyi ecotypes isolated from the Southern Ocean. Their responses were measured in terms of growth, photosynthesis, calcification, cellular geometry, and stoichiometry. The 3 ecotypes exhibited differing sensitivities in regards to seawater carbonate chemistry when cultured at the same temperature (14°C) and continuous light (110 µmol photons m -2 s -1 ). Under future ocean acidification scenarios, particulate inorganic to organic carbon ratios (PIC:POC) decreased by 38-44, 47-51 and 71-98% in morphotype A ‘over-calcified’ (A o/c), A and B/C, respectively. All ecotypes reduced their rate of calcification, but the cold-water adapted ecotype (morphotype B/C) was by far the most sensitive, and almost ceased calcification at partial pressure of carbon dioxide ( p CO 2 ) levels above 1000 µatm. We recommend that future surveys for E. huxleyi cells in the Southern Ocean should include the capability of recognising ‘naked cells’ by molecular and microscopic tools. The distinct differences in the physiological responses of these 3 dominant Southern Ocean coccolithophore ecotypes are likely to have consequences for future coccolithophore community structures and thereby the Southern Ocean carbon cycle.